EQUILÍBRIO QUÍMICO: DESENVOLVENDO CONCEITOS NO ENSINO SUPERIOR POR MEIO DE PRÁTICAS INVESTIGATIVAS - Silva, Aline Marques da (2021)
The present study is part of the Research Line - Teaching and Learning in Science and Mathematics, of the Graduate Program in Science and Mathematics Teaching, at the Franciscan University, and emerged from the difficulties and perceptions as a teacher from the difficulties understanding of students about the concepts of Chemical Equilibrium. The research aimed to investigate the contributions of practical investigative activities in the construction of the concept of chemical balance, supported by Vygotsky's cultural-historical perspective. The research subjects were students from the Chemical Engineering and Pharmacy courses at Franciscan University, in Santa Maria -RS. The guiding axis of the research was the creation of meetings called QuimiAproxima, in which investigative practices were developed, based on studies by Vygotsky (1984) on the Zone of Proximal Development (ZPD), based on teaching by investigation (inquiry) by Dewey (1997) and learning, based on Barrows' problems (1986). The research had an exploratory qualitative approach, using the following instruments for data collection: diagnostic questionnaires, pre and post-test, logbook, audio and video recording of the material produced by the students during the proposed activities. The collected data from was analyzed using Content Analysis by Bardin (2010) and the result allow us to infer that the main contributions of the proposal, in the construction of the concept of chemical balance, stand out: the curiosity and motivation of students to experience the investigative proposal and seek answers to the problem-situation, active participation and integration of most students; interaction between participants and knowledge sharing; the identification of prior knowledge and knowledge gaps; the possibility of making concepts more complex based on individual and collective reflection; skills and competence development; gradual conceptual evolution through the experience of a differentiated proposal. The research data suggest that investigative practices can gradually contribute to the understanding of the concept of chemical balance, taking into account the individualities and potential of each subject.